PEMILIHAN SEKOLAH DASAR PENERIMA BANTUAN SARANA DAN PRASARANA PEMBELAJARAN TATAP MUKA PADA ERA NEW NORMAL DENGAN METODE WEIGHTED PRODUCT DI KECAMATAN JIWAN KABUPATEN MADIUN - Ardiyantoro Cahya Putra; Moh Bhanu Setyawan; Angga Prasetyo (KOMPUTEK, 2021)
This study aims to design, build, and implement a decision support system for selecting Elementary School recipients of face-to-face learning facilities and infrastructure in the New Normal Era with the Weighted Product (WP) method in Jiwan District, Madiun Regency, East Java. The data used is secondary data in the form of public data obtained from the site http://school.data.kemdikbud.go.id/. and the number of elementary school data obtained with the boundaries of Jiwan District, Madiun Regency, amounted to 23 schools. At the stage of designing the system for this research, it is divided into three parts, namely the UML System, User Interface System and Database with ERD. The research findings show that the decision support system for selecting primary schools that receive face-to-face learning facilities and infrastructure in the New Normal Era with the WP method has several user interfaces, namely (1) User interface Login is used for security features of the Elementary School election system. (2) The Home Page user interface contains facilities for criteria data management, criteria weight data management, alternative data management, SPK value data management, user data management, and logout. (3) Criteria Data User Interface can perform criteria data management by adding and saving, changing, and deleting criteria data. (4) The Criteria Weighting Data User Interface can fill in the value of the weight of each criterion. (5) Alternative Data User Interface can add and save, change, and delete alternative data. (6) The Value Data User Interface can view and save by adding values to each alternative according to the criteria. (7) The DSS Management User Interface can make decisions by calculating the weight correction, calculating the S vector value, and calculating the V vector value. (8) User Interface Viewing Results can see the results of decision making after calculating the SPK. (9) User Management Interface Users can add, edit, and delete data from users containing usernames and passwords. Then by using the 57 item test scenarios of the blackbox method, the decision support system that was built had 100% success according to the expectations of the test scenario.